DHEA protects mitochondria against dual modes of apoptosis and necroptosis in human granulosa HO23 cells. Issue 2 (August 2017) - Tsui, Kuan-Hao; Wang, Peng-Hui; Lin, Li-Te; Li, Chia-Jung
Abstract : Because ovarian granulosa cells are essential for oocyte maturation and development, we validated human granulosa HO23 cells to evaluate the ability of the DHEA to prevent cell death after starvation. The present study was aimed to investigate whether DHEA could protect against starvation-induced apoptosis and necroptosis in human oocyte granulosa HO23 cells. The starvation was induced by treatment of serum-free (SF) medium for 4 h in vitro . Starvation-induced mitochondrial depolarization, cytochrome c release and caspase-3 activation were largely prevented by DHEA in HO23 cells. We found that treatment with DHEA can restore starvation-induced reactive oxygen species (ROS) generation and mitochondrial membrane potential imbalance. In addition, treatment of DHEA prevents cell death via upregulation of cytochrome c and downregulation of BAX in mitochondria. Most importantly, DHEA is ameliorated to mitochondrial function mediated through the decrease in mitochondrial ROS, maintained mitochondrial morphology, and enhancing the ability of cell proliferation and ROS scavenging. Our present data strongly indicate that DHEA reduces programmed cell death (apoptosis and necroptosis) in granulosa HO23 cells through multiple interactions with the mitochondrion-dependent programmed cell death pathway. Taken together, our data suggest that the presence of DHEA could be beneficial to protect human oocyte granulosa HO23 cells under in vitro culture conditions during various assisted reproductive technology (ART) programs. Free Chinese abstract: A Chinese translation of this abstract is freely available athttp://www.reproduction-online.org/content/154/2/101/suppl/DC1